The Role of Vitamin D in Pregnant Women in Birth Weight of Neonates: Peran Vitamin D pada Ibu Hamil terhadap Berat Badan Lahir Neonatus - Derevie Hendryan Moulina; Rajuddin Rajuddin; Munawar; Cut Meurah Yeni; Hilwah Nora (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: To determine the relationship between serumvitamin D levels in third trimester mothers and newbornbirthttweight.Method: The study was conducted at the maternity wardof Dr. Zainoel Abidin General Hospital in Banda Aceh,Indonesia. Maternal and infant serum vitamin D levelswere measured using the Automatic ChemiluminescenceImmunoassay Analyzer (CLIA) method. Blood samples werecollected from mothers in the third trimester and frominfants after delivery. Spearman's correlation rank test wasemployed with a confi dence level of 95%. Vitamin D levelswere categorized as suffi cient, insuffi cient, and defi cient.Results: A total of 39 pregnant women with an averageage of 30.38 ± 6.21 years participated in the study, with apredominance of 38-39 weeks of gestation (35.9%). Themean vitamin D levels in mothers and neonates were 17.4ng/mL and 17.6 ng/mL, respectively (p = 0.003, R = 0.462).The average birth weight of the babies was 3,100 grams,ranging from 2,100 grams to 4,200 grams (p = 0.185, R =0.217). Both variables showed a positive correlation withvarying strength of the relationship.Conclusion: Maternal serum vitamin D levels in the thirdtrimester exhibited a positive correlation with serum vitaminD levels in neonates with moderate strength, but therewas no correlation with birth weight. The evaluation ofmaternal third-trimester serum vitamin D levels can serve asa predictor of neonatal vitamin D levels.Keywords: birth weight, neonates, pregnancy, vitamin D. AbstrakTujuan: Untuk menilai pengaruh hubungan kadar vitaminD serum ibu trimester ketiga terhadap kadar vitamin D danberat badan neonatus yang dilahirkan.Metode: Penelitian ini studi observasional korelatif dengandesain potong lintang yang dilakukan pada kamar bersalinRSUD dr. Zainoel Abidin Banda Aceh. Pengukuran kadarvitamin D serum ibu dan bayi dilakukan dengan metodeAutomatic Chemiluminescence Immunoassay Analyzer(CLIA). Analisis data dengan melakukan Uji Spearman’scorrelation rank test untuk menilai kekuatan hubungan duavariabel.Hasil: Sebanyak 39 ibu hamil usia 30,38 ± 6,21 tahun terlibatdalam penelitian ini dengan dominasi usia kehamilan 38–39minggu (35,9%). Rerata kadar vitamin D ibu dan bayi secaraberurutan adalah 17,4 ng/mL dan 17,6 ng/mL (p = 0,003,R = 0,462). Rerata berat badan bayi yang dilahirkan adalahsebesar 3.100 gram dengan rentang 2.100 gram hingga4.200 gram (p = 0,185, R = 0,217). Kedua variabel didapatkankorelasi positif dengan kekuatan hubungan bervariasi.Kesimpulan: Kadar vitamin D serum ibu trimester ketigaberkorelasi positif terhadap kadar vitamin D serum neonatusyang dilahirkan dengan kekuatan sedang namun tidakberkorelasi terhadap berat badan lahir bayi. Kadar vitaminD serum ibu pada trimester ketiga dapat dijadikan prediktorkadar vitamin D neonatus saat dilahirkan.Kata kunci: berat badan lahir, kehamilan, neonatus,vitamin D.